Knowledge, Attitude, and Practice of Pediculus Capitis Prevention and Control and Their Predictors among Schoolchildren in Woreta Town, Northwest Ethiopia, 2018: A School-Based Cross-Sectional Study - Henok Dagne; Awel Aba Biya; Amanuel Tirfie; Walelegn Worku Yallew; Zewudu Andualem; Baye Dagnew (International Journal of Pediatrics)
Background. Pediculus capitis is a human head lice infestation, a major public health issue that is most prevalent in resource-limited countries globally. The current study aimed to assess the knowledge, attitude, and practice of pediculus capitis prevention and control and their predictors among schoolchildren in North West Ethiopia. Methods. About 402 randomly selected schoolchildren from three schools in Woreta town participated in the study from April to June 2018. The outcomes of this study were knowledge, attitude, and self-reported practice of schoolchildren about pediculus capitis prevention and control. We used EPI Info 7.1 and SPSS 21 software for data entry and analysis, respectively. Binary logistic regression was employed to test the association of covariates with the outcome/response variables. Variables with a p value <0.2 during the bivariable binary logistic regression analysis were included in the multivariable binary logistic regression analysis. Variables with p value <0.05 were declared as significantly associated with outcomes. Results. The mean age of the study participants was 10.19 (±1.62) years. About 58.8%, 45.8%, and 78.6% of the schoolchildren had better self-reported pediculus capitis prevention knowledge, attitude, and practice, respectively. Age of children [9 to 11 years (AOR=2.24, 95% C.I (1.10, 4.55)) and>12 years (AOR=3.84, 95% C.I (1.56, 9.46))], better practice (AOR=2.93, 95% C.I (1.39, 6.18)), and those who were not infested (AOR=2.25, 95% C.I (1.14, 4.44)) were predictors of knowledge regarding pediculus capitis prevention. Better practice (AOR=4.33, 95% C.I (1.69, 11.09)) and absence of infestation (AOR=2.97, 95% C.I (1.64, 5.36)) were predictors of attitude of schoolchildren about pediculus capitis prevention. Number of students in a class [51 to 56 students per classroom, AOR=4.61, 95% C.I (1.83, 11.67); 57 to 58 students per classroom, AOR=8.18, 95% C.I (2.73, 24.46)], less than five family size (AOR=2.37, 95% C.I (1.24, 4.54)), better knowledge (AOR=2.93, 95% C.I (1.32, 6.50)), desirable attitude (AOR=4.24, 95% C.I (1.60, 11.23)), and absence of infestation (AOR=3.52, 95% C.I (1.22, 10.15)) were predictors of self-reported pediculus capitis prevention practice. Conclusion. The knowledge, attitude, and practice of schoolchildren regarding pediculus capitis prevention and control were not satisfactory. To bring change, intensive efforts on factors associated with the knowledge, attitude, and practice should be encouraged.